Decreased Glucagon-Like Peptide-1 Is Associated With Calcific Aortic Valve Disease: GLP-1 Suppresses the Calcification of Aortic Valve Interstitial Cells - Xiao, Fan; Zha, Qing; Zhang, Qianru; Wu, Qihong; Chen, Zhongli; Yang, Ying; Yang, Ke; Liu, Yan (Frontiers in Cardiovascular Medicine, 2021)
Objectives: This study explores the concentration and role of glucagon-like peptide-1 (GLP-1) in calcific aortic valve disease (CAVD). Background: Calcific aortic valve disease is a chronic disease presenting with aortic valve degeneration and mineralization. We hypothesized that the level of GLP-1 is associated with CAVD and that it participates in the calcification of aortic valve interstitial cells (AVICs). Methods: We compared the concentration of GLP-1 between 11 calcific and 12 normal aortic valve tissues by immunohistochemical (IHC) analysis. ELISA was used to measure GLP-1 in serum of the Control (n = 197) and CAVD groups (n = 200). The effect of GLP-1 on the calcification of AVICs and the regulation of calcific gene expression were also characterized. Results: The GLP-1 concentration in the calcific aortic valves was 39% less than that in the control non-calcified aortic valves. Its concentration in serum was 19.3% lower in CAVD patients. Multivariable regression analysis demonstrated that GLP-1 level was independently associated with CAVD risk. In vitro, GLP-1 antagonized AVIC calcification in a dose- and time-dependent manner and it down-regulated RUNX2, MSX2, BMP2, and BMP4 expression but up-regulated SOX9 expression. Conclusions: A reduction in GLP-1 was associated with CAVD, and GLP-1 participated in the mineralization of AVICs by regulating specific calcific genes. GLP-1 warrants consideration as a novel treatment target for CAVD.